The Influence of Price, Product Quality, and Discounts on Purchase Intention of Kopi Kenangan among Psychology Students at Universitas Prima Indonesia - Mhd Farhan Rizki Lubis; Fenny Krisna Marpaung; Wahida Nur Humairoh; Angel Margaretha Hutasoit; Christin Imelda Girsang (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study examines the influence of price, product quality, and discounts on purchase intention of Kopi Kenangan among Psychology students at Universitas Prima Indonesia. This research applied a quantitative approach with an associative and explanatory research design. The population consisted of Psychology students at Universitas Prima Indonesia who had purchased Kopi Kenangan products, while the sample included 100 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed with IBM SPSS through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that price has a positive and significant influence on purchase intention, with a t-value of 2.744 and a significance value of 0.007. Product quality also has a positive and significant influence on purchase intention, with a t-value of 4.769 and a significance value of 0.000. Discounts have a positive and significant influence on purchase intention, with a t-value of 3.604 and a significance value of 0.000. Simultaneously, price, product quality, and discounts significantly influence purchase intention, as indicated by an F-value of 80.490 and a significance value of 0.000. The Adjusted R Square value of 0.707 indicates that 70.7% of the variation in purchase intention can be explained by price, product quality, and discounts, while the remaining 29.3% is influenced by other factors outside the research model. These findings suggest that Kopi Kenangan should strengthen price suitability, maintain product quality consistency, and develop attractive discount programs to increase students’ purchase intention.